PENGEMBANGAN STRATEGI QISHSHAH THARIFAH TERHADAP PEMBELAJARAN MAHARATUL KALAM - Wartiman Wartiman; Erizal Ilyas (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
This research departs from the application of the qishshah tharifah method in learning maharah al-kalam for students majoring in Arabic Language and Literature, Faculty of Adab and Humanities, UIN Imam Bonjol Padang. In this regard, this study aims to describe the application of the method in its capacity as an effort to improve the student's maharah al-kalam ability and measure the effectiveness of its application to learning outcomes. This study uses a mixing method that juxtaposes qualitative and quantitative in data collection and analysis. The results showed that the implementation of the qishshah tharifah method in learning maharah al-kalam was divided into stages of planning, organizing, actualizing, and evaluating. At the planning stage, the instructor prepares general topics that will be developed by students in the learning process. At the organizing stage, the instructor focuses on students to be more active in the lecture process. In the actualization stage, the instructor explains the general topics that will be discussed at the beginning of the meeting and then students take turns developing these topics in the form of stories. At the evaluation stage, the qishshah tharifah method applies two assessment systems, namely fluency in speaking and understanding of the content of the story being discussed. The effectiveness of the implementation of the method is reflected in student learning outcomes. In the first cycle, 76.5% of students passed and passed the minimum standard of completeness that had been set. In cycle II, 97% of students passed and passed the minimum standard of completeness. This is very different from the results of the pre-test that was held before the action, where the number of students who passed was only 39%.